Pengaruh Corporate Social Responsibility (CSR) Terhadap Persistensi Laba Pada Perusahaan Sub Sektor Advertising Printing Media, Hotel, Restoran, Pariwisata, Jasa Komputer, dan Perdagangan Lainnya - Anastasya Debbie Aliantho; Juniarti Juniarti (Business Accounting Review, 2016)
Research about the affect of Corporate Social Responsibility (CSR) with earnigs persistence are still very rare. Among them were Belkaoui (2004), Salewski (2004), Laksmana dan Yang (2009), Muttakin et al., (2015). These studies had not been done on Sub Sector Company Advertising Printing Media, Hotel, Restaurant, Tourism, Computer Services, and Other Trade. The aim of this study was to examine the affect of CSR on earning persistence on Sub Sector Company Advertising Printing Media, Hotel, Restaurant, Tourism, Computer Services, and Other Trade. Sample for this study start form 2010 until 2014 with 17 companies by using control variables firm size and leverage. The data in this study were processed by using SPSS version 22. This study succeeded to prove the positive effect of CSR to earning persistence, but this study also have not found a significant relationship between firm size and leverage with earnings persistence.